Promoting health equity through cross-sector strategies: the integration of communication public health - Lopez, Leslie; Warren, Sarah; Anthony, Teresa; Coco, Laura (Frontiers in Public Health, 2025)
Communication is a fundamental human experience at both inter-and intrapersonal levels, deeply intertwined with societal development. Because of the integral role of communication in society, challenges in communication—whether due to differences, disorders, or environmental factors—can create significant barriers to full societal participation. Rather than viewing these challenges solely through the lens of “disability,” recognizing communication health as a distinct and essential aspect of public health is crucial for addressing these barriers and advancing health equity. This viewpoint introduces the concept of Communication Public Health, advocating for an integrated approach that unites the fields of communication sciences and disorders and public health to address communication health as a social determinant of health. It presents a conceptual framework that emphasizes collaboration across the education, employment, housing, and community sectors, highlighting the importance of perceiving communication challenges as modifiable barriers to full societal participation. It aims to offer insight and debate, and mobilize public health professionals to recognize and prioritize communication health, offering a comprehensive approach that considers both individual and societal needs. By establishing Communication Public Health as a new and distinct entity within public health infrastructure, we can better address the full spectrum of communication needs, from individuals with communication disorders and differences to those with healthy communication abilities. This perspective article format allows us to synthesize underexamined intersections between communication sciences and public health, and to advocate for an emerging framework in the absence of an established empirical evidence base.